Space Invaders: border crossing in Dan Halter's Heartland. Issue 4 (1st October 2016) - Hennlich, Andrew J.
Abstract: Using springstone sculpture and woven paper photographs, the Zimbabwean-born artist Daniel Halter draws from African craft traditions to expose the precariousness of migrant experiences in South Africa. Halter, who lives in Cape Town, exposes the ironic tensions between hostility towards migrants and metaphors of inclusiveness in the post-apartheid nation. This essay reads metaphors of belonging, border crossing, and nationalism evoked by Halter's materials and modes of production. Building from Ranjana Khanna's work on demetaphorization – an undoing of discourses of community – and Edward Casey and Mary Watkin's analysis of the border as always already undone by its lived functions, the essay argues Halter addresses the immigrant's position uncovering the borderland as both a porous zone and a metaphor of exclusion. By weaving, Halter addresses this condition through an interdependency that, following Derrida's work on hospitality, offers a framework to reconsider discourses of citizenship and nationalism in southern Africa.